The Need for Elderly and Caregivers Perspective in the Model for Fall Prevention Strategies: The Malaysian Context - Justine, Maria (Highlights on Medicine and Medical Research Vol. 4, 2021)
Falls incidence is a public health issue among older people as it causes morbidity and mortality. Despite the growing evidence in the prevention of falls in older people, however, most interventions were developed based on the perspective of the health care providers and mostly targeting the physiological risk factors. Limited studies have included the perspective of older people and their caregivers in understanding falls and its preventions. It is important to know how older people and their caregivers perceived falls incidence, understand the risk factors and how they should prevent falls as this may empower them to practice the fall prevention strategies. This article briefly examined the current evidence on fall prevention strategies and the model of care for older people at risk of falls. The article then identified the gaps in the previous studies and suggested the conceptual model and theoretical model to guide future studies.